An overview of the genus Prismatomeris: Phytochemistry and biological activity - Ninh The Son (Faculty of Pharmacy, Cairo University, 2017)
Genus Prismatomeris belongs to Rubiaceae family, with interesting secondary metabolites, comprising main classes of compounds anthraquinones, iridoids, triterpenoids and their derivative glycoside. Prismatomeris species has been employing as folk medicines against hepatitis, stomachaches, pneumoconiosis, poultice to fresh wounds, bloody vomiting, etc. Many bioactive reports such as cytotoxic assay, antifungal, antimalarial, or oedema inhibitory activity, indicate either Prismatomeris extracts or isolated compounds to become valuable resources for natural new drug developments. However, no evidences are reported for general view about this genus. In current paper, we exhibit overview of major chemical components and biological evaluations from this genus. Basing on this view, it helps us understand the traditional values of these medicinal plants, and guideline for future researches.